Pengembangan Paket Latihan dan Penilaian Berbantuan Komputer untuk Pembelajaran Alat Ukur Mekanik Presisi - Surono Surono; Chrisna Tri Harjanto (Department of Mechanical Engineering Education, 2019)
This study aims to: (1) formulate the steps to develop a computer-aided training and assessment packages for the learning materials of precision mechanical measuring devices, (2) obtain a computer-aided training and assessment packages that are applicable for use in the learning process. The research type is Research and Development (R&D), which was referred to the Borg & Gall model modified by Sukmadinata (2009), and the model developed by Sugiyono (2011). The research was conducted at SMK Negeri 2 Wonosari. The data collection were using questionnaire instruments and computer-aided training and assessment packages. The research data were analyzed using descriptive statistical analysis techniques. The results of this study are as follows. (1) The steps in developing computer-aided training and assessment packages are preliminary studies, production, product evaluation, and dissemination; (2) The developed computer-aided training and assessment packages are suitable for use in the learning process based on the expert validation and students' responses. The validation from the material learning experts resulted in a mean score of 4.46 (excellent category); validation from the assessment experts obtained a mean score of 4.41 (excellent category), and validation from the learning media experts obtained a mean score of 4.55 (excellent category). The mean score of students' responses in the beta test was 4.06 (good category), and the mean score in the summative evaluation was 4.00 (good category).Penelitian ini bertujuan untuk: (1) merumuskan langkah-langkah pengembangan paket latihan dan penilaian berbantuan komputer untuk materi pembelajaran alat ukur mekanik presisi, (2) mendapatkan paket latihan dan penilaian berbantuan komputer yang layak digunakan dalam pembelajaran. Jenis penelitian ini adalah research and development (R&D), mengacu pada model Borg & Gall yang telah dimodifikasi oleh Sukmadinata (2009) dan model yang dikembangkan Sugiyono (2011). Lokasi penelitian di SMK Negeri 2 Wonosari. Instrumen pengumpulan data yang digunakan adalah angket, serta paket latihan dan penilaian berbantuan komputer. Data penelitian dianalisis menggunakan teknik analisis statistik deskriptif. Hasil penelitian ini adalah sebagai berikut. (1) Langkah-langkah pengembangan paket latihan dan penilaian berbantuan komputer dilakukan melalui empat tahap, yaitu studi pendahuluan, produksi, evaluasi produk, dan diseminasi; (2) Paket latihan dan penilaian berbantuan komputer yang dikembangkan layak digunakan dalam pembelajaran berdasarkan validasi ahli dan tanggapan siswa. Validasi oleh ahli materi memperoleh rerata skor 4,46 dengan kategori sangat baik; validasi oleh ahli evaluasi memperoleh rerata skor 4,41 dengan kategori sangat baik; dan validasi oleh ahli media memperoleh rerata skor 4,55 dengan kategori sangat baik. Rerata skor tanggapan siswa pada beta test adalah 4,06 dengan kategori baik, dan rerata skor pada evaluasi sumatif adalah 4,00 dengan kategori baik